Variables asociadas al nivel de gravedad del dengue en usuarios hospitalizados en infectología del Hospital Regional de Loreto Iquitos 2022 - Nakagawa Valverde, Nelly (2024)
The objective was to determine the variables associated of severity of Dengue in users hospitalized in Infectology at the Regional Hospital of Loreto 2022. The method used was the quantitative and correlational, retrospective, descriptive design. For the study, a sample of 113 clinical records of users with Dengue treated in Infectology at the Loreto Regional Hospital was used. The technique was the documentary review and the instruments were the Personal and Clinicopathological Characteristics Data Sheet and the Dengue Severity Level Classification Data Sheet. For the correlational analysis, the Chi Square statistical test was used with a significance of α = 0.05. The results were: 61.9% were between 18 and 29 years old, 56.6% were women, 59.3% reached secondary level, 45.1% were housewives, 72.6% came from of urban areas, 85% had no history of dengue, 69% had an illness time of 4 to 7 days, 90.3% had a hospitalization time of less than 7 days, 12.4% presented hypertension and 92.9% presented a level of dengue with an alarm sign. In conclusion, a significant association was demonstrated between the level of severity of dengue and age (p < 0.01) p = 0.006, sex (p < 0.05) p = 0.010, and origin (p < 0.05). p= 0.013, time of illness before hospitalization p= 0.003 (p< 0.01), time of hospitalization p = 0.000 (p< 0.01 and comorbidity (Hypertension p= 0.005 (p< 0.001) and kidney disease p = 0.000 (p < 0.001).